Pembandaran dan perkembangan wilayah metropolitan lanjutan Lembah Klang-Langat, Malaysia - Katiman Rostam (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
The process of economic globalisation and urbanisation is currently taking place in and around Southeast Asian metropolitan regions. In Malaysia, the Klang-Langat Valley is an extended metropolitan region (EMR). The region is expanding very rapidly. The process of urban sprawl in the EMR tends to favour the southern corridor. This paper discusses the growth of manufacturing and service activities and their impacts on settlements located in the peripheral areas of the EMR. Analysis of data gathered from the Population and Housing Census of Malaysia and various economic reports indicates that the proces of economic development and urbanisation in the Klang-Langat Valley EMR is mainly concentrated in the core and internal areas of the region. However there is a clear indication that such development is shifting towards the peripheries. Various advanced producer services such as research and development, computeration, banking, insurance, fast fowarding and delivery services which are vital for manufacturing processes have emerged to strengthen the functions of metropolitan city of Kuala Lumpur. Availabality of these services are facilitated by the most up-to date technology which could benefit firms located in the region in terms of urbanisation economy. Many more corporate headquaters are established in the core and internal zones while at the same time the manufacturing and public services relocate their activities to the peripheries of the EMR. The shift of economic activities to the peripheries has brought about change and urbanisation of the area, resulting in the growth of many housing schemes and planned small towns in the peripheries. However, characteristics of these settlements are clearly distinct from those settlements known to many writers as desakota which used to be found in many metropolitan cities of Southeast Asia. Although Kuala Lumpur has not been regarded as a mega city, in the near future, with the fast expansion of her built-up areas, the city will emerge as one of most prominent conurbations in this region.